Cynicism from Diogenes to Dilbert - Cutler, Ian, 1948-; Gabriel, Yiannis, 1952- (Jefferson, N.C. : McFarland & Company, 2005)
"The book focuses on significant periods of historical change, such as the Renaissance, and the historical cynics responsible for several seminal social ideas, including cosmopolitanism, asceticism, and parrhesia. The author claims that aspects of Greek cynicism are present in contemporary society, offering a positive strategy for living in a hostile world"--Provided by publisher.
Cynisme door de eeuwen heen, van Socrates ... tot de Benny Hill Show!
Classical foundations of cynicism -- Renaissance cynicism : the limits of cynicism -- Nietzschean cynicism : the link between the ancient and the modern forms -- Postmodern cynicism -- Return of the dog cynics : 20th century performance art -- Contemporary faces of cynicism : action, laughter and silence -- Cynical responses to the 21st century.
Includes bibliographical references (p. 201-219) and index.
Keywords: Cynicism -- Social aspects; Cynics (Greek philosophy).